2020
DOI: 10.2478/dcse-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Professional Development Needs: A Q Method Analysis

Abstract: This study aims to determine the professional development needs of teachers working in different subject domains. In this context, the sample of this study was 35 teachers working in state schools in Cappadocia provinces of Turkey. Q method analysis which includes qualitative and quantitative processes is used in this study. The professional development needs of the teachers is discussed under four main themes; instructional development, scientific field development, personal development, and organizational de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 35 publications
5
15
0
1
Order By: Relevance
“…3 In addition, for the curriculum development domain, course plans and lesson plans were given the least priority in the present study, which is in line with other studies. 3,5,11,15,16 However, Shah et al…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…3 In addition, for the curriculum development domain, course plans and lesson plans were given the least priority in the present study, which is in line with other studies. 3,5,11,15,16 However, Shah et al…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, other studies have reached similar conclusions about faculty need for personal development 16,19–21 . Nonetheless, curriculum design received less than half the vote in the Karimi research, 6 and teachers reported feeling most effective in personal development in the Yenen study's 3 …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Bu çalışmada, klinik süpervizörlerin öznel bakış açılarını ortaya çıkarmak için Q metodolojisi kullanılmıştır. Karma bir araştırma yöntemi olarak Q, öznelliğe odaklanması ve katılımcıların veri analizinin merkezinde yer alması (kişi bazında faktör analizi) nedenleriyle son on yılda sosyal bilimlerde yaygın bir metodoloji haline gelmiştir (Yenen ve Yöntem, 2020). Bu alanda çalışan araştırmacıların, Q'nun teorik temellerine vurgu yaparak (bkz.…”
Section: öNeriler Ve Sınırlılıklarunclassified